Dynamic control of the lumbopelvic complex; lack of reliability of established test procedures - Henriksen, Marius (Springer-Verlag, 2006)
Impairment of the dynamic control of the lumbopelvic complex in LBP has gained increased focus both clinically and experimentally. The objectives of this study were to determine the reliability of inclinometry as a measure of dynamic lumbopelvic control. Lumbopelvic reposition accuracy during pelvic tilts was measured in 39 healthy subjects using an inclinometer attached to the skin at S2 level. The reposition accuracy was measured in sitting, standing and supported standing. Tests were performed three times with a 20 min recess between tests. Only data from the last two test sequences were used in order to account for learning effects. Intraclass correlation coefficients were low for the sitting (0.54) and supported standing positions (0.36). In the standing position, a significant difference between test and retest was observed (P = 0.003) and further reliability analysis was therefore abandoned. It is concluded that inclinometry is not reliable for measuring the dynamic lumbopelvic control in any of the test positions and prior work utilising inclinometry to evaluate dynamic lumbopelvic control should be interpreted with caution.